2004
DOI: 10.1111/j.1365-2133.2004.06211.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of actinic keratosis at varying fluence rates: assessment of photobleaching, pain and primary clinical outcome

Abstract: Our results imply that the photobleaching rate and primary treatment outcome are dependent on fluence rate, and that a low fluence rate (30 mW cm(-2)) seems preferable when performing PDT of AK using noncoherent light sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
5
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 42 publications
10
121
5
2
Order By: Relevance
“…Our report has shown that the 4 parameters cannot be easily correlated, although PpIX fluorescence intensity, photobleaching and the clinical outcome can be. Surprisingly, to our knowledge [29,44,45,46], only a very limited number of publications have addressed this issue in detail. Our report demonstrates that this correlation, although not perfect, does exist, including in the medium to long term (>33 months), and that it can be measured with a set-up mainly made of commercially available parts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our report has shown that the 4 parameters cannot be easily correlated, although PpIX fluorescence intensity, photobleaching and the clinical outcome can be. Surprisingly, to our knowledge [29,44,45,46], only a very limited number of publications have addressed this issue in detail. Our report demonstrates that this correlation, although not perfect, does exist, including in the medium to long term (>33 months), and that it can be measured with a set-up mainly made of commercially available parts.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is a possibility that measuring the PS's photobleaching (i.e. the reduction in the fluorescence intensity of PpIX, caused by the PDT irradiation) may be a useful way to evaluate - and adjust - the administration of the PDT light dose [27,28,29,30,31]. If demonstrated, this simple way to individualize treatment parameters would render more complicated approaches unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing oxygen concentration, the quantum yield of singlet oxygen is also decreasing (42). Therefore, the light excitation of photosensitizers in photodynamic therapy of cancer is fractionated by using irradiation breaks of several minutes to allow oxygen supply to tumor areas (24,(43)(44)(45). This procedure was also used with biofilms of Streptococcus mutans, which were efficiently inactivated by light dose fractionation (46).…”
Section: Singlet Oxygen Luminescence For Variable and High Bacterial mentioning
confidence: 99%
“…The experience of pain varies from patient to patient, but studies have suggested that the factors of importance for the discomfort of the patients are type of lesion, localization of lesion, size of area treated, sex, intensity of light delivery and light source [5, 6]. …”
Section: Introductionmentioning
confidence: 99%